Cost-effectiveness analysis of serplulimab plus chemotherapy in the first-line treatment for PD-L1-positive esophageal squamous cell carcinoma in China - Liu, Shixian; Jiang, Nana; Dou, Lei; Li, Shunping (Frontiers in Immunology, 2023)
Objective: The ASTRUM-007 trial (NCT03958890) demonstrated that serplulimab plus chemotherapy administered every 2-week significantly improved progression-free and overall survival in patients with previously untreated, programmed death-ligand 1 (PD-L1) positive advanced esophageal squamous-cell carcinoma (ESCC). This study was aimed to investigate the cost-effectiveness of serplulimab plus chemotherapy in the first-line treatment of PD-L1-positive advanced ESCC. Methods: A partitioned survival model with a 2-week cycle and a 10-year time horizon was constructed from the Chinese healthcare system perspective. The survival data, direct medical costs and utilities were derived from the ASTRUM-007 trial and published sources. Total costs, quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs) were calculated. Scenario, one-way and probabilistic sensitivity analyses were performed to assess the uncertainty around model parameters. Results: Compared with chemotherapy, serplulimab plus chemotherapy provided additional 0.27 QALYs with an incremental cost of 33,460.86, which had an ICER of 124,483.07 per QALY. The subgroup analyses revealed that the ICERs of serplulimab plus chemotherapy were 134,637.42 and 105,589.71 in advanced ESCC patients with 1 ≤ CPS < 10 and CPS ≥ 10, respectively. The price of serplulimab, patient weight, utility values and discount rate were the most influential parameters on base-case results. At a willingness-to-pay threshold of three times per capita GDP (38,351.20) in 2021, the probability of serplulimab plus chemotherapy being cost-effective was 0% compared with chemotherapy. When the price of serplulimab decreased by 70%, the probabilities of serplulimab plus chemotherapy being cost-effective were 72.10%, 55.24% and 93.23% in advanced ESCC patients with PD-L1-positive, PD-L1 1≤CPS<10 and CPS≥10, respectively. Conclusion: Serplulimab plus chemotherapy in the first-line treatment for PD-L1-positive advanced ESCC might not be cost-effective in China.